Assemblages of Acari in shallow burials: mites as markers of the burial environment, of the stage of decay and of body-cadaver regions - Jas K. Rai; Brian J. Pickles; M. Alejandra Perotti (Experimental and Applied Acarology, 2021)
The burial of a cadaver results in reduced arthropod activity and disruptions in colonisation patterns. Here, the distribution and diversity of mite taxa was studied across decomposition stages of shallowly buried pig carcasses ( Sus scrofa domesticus ). In total 300 mites (88 species) were collected from three pig shallow graves compared to 129 mites (46 species) from control (bare) soil samples at the same depth. A successional pattern of Acari higher taxa and families was observed, and species richness and biodiversity fluctuated throughout decomposition, whereas active decay showed the greatest biodiversity. Mesostigmata mites were the most abundant in ‘cadaver soils’ with a significant difference in the abundance of Parasitidae mites, whereas Oribatida mites (true soil mites) were the most abundant in control soils. Certain mite species were significantly associated with decay stages: Cornigamasus lunaris with ‘bloated’, Gamasodes spiniger with ‘active’, Eugamasus sp. and Lorryia reticulata with ‘advanced’, and Macrocheles matrius and Ramusella clavipectinata in ‘dry’. Scheloribates laevigatus was a marker of bare soil at a shallow depth and Vulgoramasus remberti of buried decomposition, not specific to any decay stage. Analysis of mite assemblages associated with head, torso and posterior body showed that Parasitus evertsi and M . matrius are attracted to beneath the thighs, whereas L . reticulata to beneath the head. This study highlights the value of mites as indicator species of decomposition and its stages, confirming (1) a succession of Acari on buried remains and (2) species specificity to body regions.